Method for Fast and Complexity-Reduced Asymmetric Image Compression - Bilinskis, I.; Skageris, A.; Sudars, K. (Elektronika ir Elektrotechnika, 2011)
Standartised image compression/reconstruction algorithms are symmetric in the sense that the computational complexities characterizing image compression and reconstruction stages are almost equal. An approach to assymetric image compression is suggested and discussed. Image compression performed according to this approach is extremely simple and the computational burden of the commpression/reconstruction task is shifted assymetrically to the image reconstruction stage. This approach, based on typical DASP methods, is described and discussed. The described image compression/reconstruction algorithms have been evaluated both on the basis of computer simulations and experimental studies and the obtained results are given. Ill. 2, bibl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.303